2020
DOI: 10.1371/journal.pntd.0008290
|View full text |Cite
|
Sign up to set email alerts
|

The excretory/secretory products of fifth-stage larval Angiostrongylus cantonensis induces autophagy via the Sonic hedgehog pathway in mouse brain astrocytes

Abstract: Angiostrongyliasis is induced by the nematode Angiostrongylus cantonensis and leads to eosinophilic meningitis and meningoencephalitis in humans. Excretory-secretory products (ESPs) are important investigation targets for studying the relationship between hosts and nematodes. These products assist worms in penetrating the blood-brain barrier and avoiding the host immune response. Autophagy is a catabolic process that is responsible for digesting cytoplasmic organelles, proteins, and lipids and removing them th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Finally, we suggest that the M2 polarization promotes repair of the injured nervous tissue. Astrocyte-mediated IL-6-driven formation of the glial scar, which we observed 14-21 dpi, is commonly considered the primary mechanism of the nervous tissue repair, also known from other helminth neuroinfections [22,98,99]. However, M2 microglia/macrophages promote tissue regeneration and remyelination by driving differentiation of oligodendrocytes [100,101].…”
Section: Plos Pathogensmentioning
confidence: 59%
“…Finally, we suggest that the M2 polarization promotes repair of the injured nervous tissue. Astrocyte-mediated IL-6-driven formation of the glial scar, which we observed 14-21 dpi, is commonly considered the primary mechanism of the nervous tissue repair, also known from other helminth neuroinfections [22,98,99]. However, M2 microglia/macrophages promote tissue regeneration and remyelination by driving differentiation of oligodendrocytes [100,101].…”
Section: Plos Pathogensmentioning
confidence: 59%
“…Previous studies have shown that Angiostrongylus cantonensis ES could reduce cell survival. Also, the use of autophagy activator has been shown to enhance cell viability through the activation of the autophagy mechanism in astrocytes [ 15 ]. Given that ES of T .…”
Section: Resultsmentioning
confidence: 99%
“…Host cell autophagy induced by Toxoplasma gondii and Plasmodium is exploited by the parasites to acquire nutrients, which contributes to their growth and development [ 13 , 14 ]. Recent studies have also revealed that the inhibition of autophagy or excess autophagy can induce cell apoptosis in Echinococcus granulosus [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their importance in nematode pathogenesis, ESPs are an important target in the investigation of host-parasite relationships and research in vaccine candidates and therapeutic targets. In previous investigation, we demonstrated that A. cantonensis ESPs can stimulate oxidative stress, autophagy, ER stress, and cell apoptosis in astrocytes [36][37][38]. However, we used proteomic analysis to profile, identify, and characterize the proteins in the A. cantonensis L5 ESPs.…”
Section: Discussionmentioning
confidence: 99%